2019
DOI: 10.3390/ijms20051078
|View full text |Cite
|
Sign up to set email alerts
|

Participation of NADPH Oxidase-Related Reactive Oxygen Species in Leptin-Promoted Pulmonary Inflammation: Regulation of cPLA2α and COX-2 Expression

Abstract: Obesity is a worldwide epidemic problem and correlates to varieties of acute or chronic lung diseases such as acute respiratory distress syndrome, chronic obstructive pulmonary disease, and pulmonary fibrosis. An increase of leptin, a kind of adipokine, in lean mice plasma has been found to impair immune responses and facilitate the infection of Klebsiella pneumoniae, resulting in increased pneumonia severity. Also, a higher leptin level is found in exhaled breath condensates of obese or asthmatic subjects, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 52 publications
0
11
0
1
Order By: Relevance
“…ROS are also required for the maintenance and differentiation of primary lung fibroblasts for lung tissue homeostasis [ 19 ]. However, a continuously excessive production of ROS (oxidative stress) in the lung by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) may result in tissue injury and dysregulated injury/repair and ultimately lead to chronic pulmonary diseases, such as pulmonary fibrosis [ 19 , 20 ]. In addition, exposure to silica dust was demonstrated to induce ROS production and lung injury in animal models [ 17 , 21 ], suggesting a pathogenetic role of ROS in the development of silicosis.…”
Section: Introductionmentioning
confidence: 99%
“…ROS are also required for the maintenance and differentiation of primary lung fibroblasts for lung tissue homeostasis [ 19 ]. However, a continuously excessive production of ROS (oxidative stress) in the lung by nicotinamide adenine dinucleotide phosphate (NADPH) oxidase (NOX) may result in tissue injury and dysregulated injury/repair and ultimately lead to chronic pulmonary diseases, such as pulmonary fibrosis [ 19 , 20 ]. In addition, exposure to silica dust was demonstrated to induce ROS production and lung injury in animal models [ 17 , 21 ], suggesting a pathogenetic role of ROS in the development of silicosis.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the nephrotoxic agent, aristolochic acid I, increases protein abundance of the NADPH oxidase subunits NOX4, p47 phox , p22 phox and 3-nitrotyrosine in rats within 8 to 24 weeks [17]. Moreover, upregulation of intracellular ROS promotes the expression of inflammatory genes, including cPLA2 and COX-2 [18,19]. In fact, ameliorating oxidative stress via modulating forkhead box class O1 (FOXO1) expression attenuated high glucose-induced renal proximal tubular cell injury [20].…”
Section: Introductionmentioning
confidence: 99%
“…In the present study, the release of NO and the expression of iNOS could be suppressed by niloticin. In addition, niloticin could also downregulate the expression of COX-2, which is related to the severity of inflammation [34]. A previous study showed that COX-2-deficient rats could delay the infiltration of leukocytes into important organs and resist infection mediated by LPS [35].…”
Section: Discussionmentioning
confidence: 99%